IS BARIATRIC SURGERY A TREATMENT FOR HYPERTENSION AND FOR THE OTHER COMPONENTS OF THE METABOLIC SYNDROME?. (April 2021) - Lechea, Elena; Popescu, Mihaela; Ploesteanu, Rodica; Dimulescu, Doina; Catalin, Copaescu
Abstract: Objective: Our objective is to determine the impact of weight loss obtained by bariatric surgery on the components of the metabolic syndrome such as visceral obesity, atherogenic dyslipidemia, glycemic disorders and hypertension secondary. Design and method: This is a retrospective pilot study including 59 patients subjected to bariatric surgery (gastric sleeve laparoscopy) during 2016 at Ponderas Academic Hospital Bucharest, Romania. We have reviewed the hospital database for blood tests, diabetes, cardiologic and surgery consultations before surgery and at 12 months follow up. We tracked the evolution of the following parameters: body mass index, waist circumference, weight, blood sugar, triglycerides, high density cholesterol, low density cholesterol, glycated hemoglobin, liver enzymes, the presence or absence of hypertension, dyslipidemia and diabetes and the necessary for antihypertensive, lipid lowering and antidiabetic treatment. 51 of the patients (86%) were hypertensive, 48 of them had chronic antihypertensive oral treatment and 3 of them were equilibrated by low salt diet. Results: The need for antihypertensive treatment was reduced by 60%, only 19 out of 48 patients still had chronic blood pressure lowering treatment at 12 moths follow up. Patients still on treatment had lower doses or fewer classes of the initial drugs. BMI decreased by 38%; waist was reduced by 31%, weight declined by 41%; blood sugar was lowered by 16%, triglycerides decreased by 37%; high density cholesterol increased by 18%, low density cholesterol decreased by 9%. In diabetic patients glycated hemoglobin decreased by 28% and the necessity for antidiabetic medical treatment dropped by 69%. The decline was statistically significant for al variables (P < 0.001) except for low density cholesterol. Blood sugar values registered a more accelerated decrease in the first 6 months. Conclusions: Weight loss obtained by bariatric surgery in this study, improves metabolic syndrome in all of its components. The lower decrease in LDL Cholesterol in our study can be partly explained by the borderline values at the baseline. Longer retrospective analyses and prospective studies, expanding the number of patients are necessary and in progress, in order to determine the recurrence or new onset of hypertension.